Evaluation of clinical efficacy of tilmicosin in the treatment of respiratory system infections of calves - Mahmut Ok; Hasan Hüseyin Hadimli; Merve İder (Eurasian Journal of Veterinary Sciences)
Aim: The aim of this study was to evaluate the clinical efficacy of tilmicosin in the treatment of respiratory system infections of calves. Materials and Methods: This study was performed on 30 calves with respiratory system infections. Bronchoalveolar lavage (BAL) fluid samples were taken from the calves. Microbiological examinations of BAL fluid samples were performed and antibiotic susceptibilities of the agents were determined. A single dose of tilmicosin (10 mg/kg SC) was administered to each calves. Results: While bacterial growth was not observed in 11 of 30 BAL samples, bacterial growth of 19 was detected. Pasteurella multocida (P. multocida) was isolated in 14 of the sample. Remaining bacteria were 3 Trueperella pyogenes (T. pyogenes) and 2 Escherichia coli (E. coli). Amoxicillin, sefquinom, marbofloxacin, gamithromycin and tilmicosin were found to be effective antibiotics. Conclusion: As a result, the dominant bacterium in respiratory system infections is Pasteurella multocida and also tilmicosin was effective in the treatment of respiratory diseases of calves.